2022
DOI: 10.1021/acs.langmuir.2c00437
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field-Assisted Fission of a Ferrofluid Droplet for Large-Scale Droplet Generation

Abstract: With the presence of an external magnetic field, a ferrofluid droplet exhibits a rich variety of interesting phenomena notably different from nonmagnetic droplets. Here, a ferrofluid droplet impacting on a liquidrepellent surface is systematically investigated using high-speed imaging. The pre-and post-impact, including the droplet stretching, maximum spreading diameter, and final impact modes, are shown to depend on the impact velocity and the magnitude of the external magnetic field. A scaling relation invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…A substantial collection of scholarly work has previously been reported on the interfacial dynamics and its characterization of ferrofluid droplets. Guo et al focused on examining the impact of magnetic fields on ferrofluid droplets positioned on a modified hydrophobic surface. They observed that the presence of superhydrophobic surfaces enhances the mobility of ferrofluid droplets as a result of their reduced surface energy and restricted adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…A substantial collection of scholarly work has previously been reported on the interfacial dynamics and its characterization of ferrofluid droplets. Guo et al focused on examining the impact of magnetic fields on ferrofluid droplets positioned on a modified hydrophobic surface. They observed that the presence of superhydrophobic surfaces enhances the mobility of ferrofluid droplets as a result of their reduced surface energy and restricted adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…Ferrofluid has demonstrated a wide range of studies, including encapsulation, mixing, droplet manipulation, evaporation, and cell sorting . The impact dynamics of magnetic droplets on a nonmagnetic substrate is widely studied in the literature, which involves the effect of magnetic field on the dynamics of droplet spreading and postimpact self-assembly. In this regard, Shyam et al have studied the impact dynamics of a water-based ferrofluid on PDMS substrate. It is found that upon impact, the ferrofluid droplet undergoes Rosensweig instability and exhibits several regimes of equilibrium configurations .…”
Section: Introductionmentioning
confidence: 99%